Influence of the Sound Source’s Position on the Stage on the Speech Perception in the Auditorium - Stefan Brachmański; Piotr Kozłowski (Applied Sciences)
Constant efforts to achieve the best possible speech intelligibility during theatre performances were the motivation for the research presented in this article. The acoustic conditions in a theatre hall depend not only on the design of the room acoustics, but also on the stage decoration and the positioning of the sound source (actor) on stage. The ACR (Absolute Category Rating) method recommended by the ITU was used to investigate the influence of the decorations and the position of the speaker on stage on the subjective evaluation of the listeners’ perception of speech. Subjective tests were carried out in situ and in the laboratory based on recordings made in the facility that was the subject of the measurements. An extensive analysis of the results was carried out, taking into account individual aspects of the tests, such as the type of decoration, speaker position, listener position, and the way the recording was made. Based on the discussion of the results, the conclusions are presented.